1978
DOI: 10.1021/bi00596a029
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the macrolide antibiotic chlorothricin: basic building blocks

Abstract: The biosynthesis of chlorothricin (I), a macrolide antibiotic isolated from Streptomyces antibioticus Tü 99, has been studied by feeding experiments with 14C- and 3H-labeled precursors. Acetate and propionate, but not methionine and mevalonate, were incorporated into the macrocylic aglycone of the antibiotic. Glucose and the various carbon atoms of tyrosine, except the carboxyl carbon, also contributed label to the aglycone. Glucose also seems to be a specific precursor of the 2-deoxyrhamnose moiety, probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
(23 reference statements)
3
20
0
Order By: Relevance
“…A similar labeling pattern was found in the biosynthetic study of CHL (10,22), and the three remaining carbons at corresponding positions were confirmed to be derived from the glycerol (17), suggesting that a common strategy involves the incorporation of a glycerol-derived 3-C unit with a polyketide chain to form the aglycones in spirotetronate biosynthesis. In 2006, we reported the cloning and characterization of the chl gene cluster as the first genetic model to propose the biosynthetic pathway in this family (11).…”
supporting
confidence: 75%
“…A similar labeling pattern was found in the biosynthetic study of CHL (10,22), and the three remaining carbons at corresponding positions were confirmed to be derived from the glycerol (17), suggesting that a common strategy involves the incorporation of a glycerol-derived 3-C unit with a polyketide chain to form the aglycones in spirotetronate biosynthesis. In 2006, we reported the cloning and characterization of the chl gene cluster as the first genetic model to propose the biosynthetic pathway in this family (11).…”
supporting
confidence: 75%
“…Earlier biosynthetic studiese 6,7) have established the biosynthetic origin for most of the carbon frameworks of these components, as summarized in Scheme 1. The modified 6-methylsalicylic acid comes from 4 acetate-malonate units via the polyketide pathway, with contribution of the additional 0-methyl group by methionine, and the two 2,6-dideoxyhexose moieties are derived directly from glucose.…”
Section: Chlorothricin (I) Is An Unusual Macrolide Antibiotic Producementioning
confidence: 99%
“…It was reported that the aglycone of chlorothricin is synthesized via the polyketide route and one of its hypothetical intermediates has the same basic skeletal structure as that of tetrocarcin A. 6 ) Although acetate and propionate could not stimulate the production of tetrocarcin A, it is very likely that tetrocarcin A is synthesized via the polyketide route and experiments to substantiate these hypotheses are in progress using labeled acetate and propionate by 14C and 13e. It is very interesting that L-Ieucine and its corresponding keto acid (a-ketoisocaproic acid) stimulated the production of tetrocarcin A, but retarded the growth of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that chlorothricin is synthesized via the polyketide route from acetic and propionic acid. 6 ) Therefore the effects of these organic acids and others on tetrocarcin A production were studied. As shown in Table VI, acetic acid, propionic acid and other organic acid did not promote tetrocarcin A production but were slightly effective for growth of the organism.…”
Section: Effects Of Organic Acidsmentioning
confidence: 99%